2017
DOI: 10.1186/s12872-017-0543-0
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure in patients with coronary heart disease: Prevalence, characteristics and guideline implementation – Results from the German EuroAspire IV cohort

Abstract: BackgroundAdherence to pharmacotherapeutic treatment guidelines in patients with heart failure (HF) is of major prognostic importance, but thorough implementation of guidelines in routine care remains insufficient. Our aim was to investigate prevalence and characteristics of HF in patients with coronary heart disease (CHD), and to assess the adherence to current HF guidelines in patients with HF stage C, thus identifying potential targets for the optimization of guideline implementation.MethodsPatients from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…However, most of the studies included in our analysis were adjusted using the propensity score matching system, which adds validity to our results. Second, lower ejection fraction and higher New York Heart Association (NYHA) class are independent predictors of increased mortality in patients with heart failure [39, 40]. In our meta-analysis, influenza seemed to increase the mortality of patients with heart failure, but only 2 of the included studies reported the ejection fraction or the NYHA class of their patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, most of the studies included in our analysis were adjusted using the propensity score matching system, which adds validity to our results. Second, lower ejection fraction and higher New York Heart Association (NYHA) class are independent predictors of increased mortality in patients with heart failure [39, 40]. In our meta-analysis, influenza seemed to increase the mortality of patients with heart failure, but only 2 of the included studies reported the ejection fraction or the NYHA class of their patients.…”
Section: Discussionmentioning
confidence: 90%
“…Finally, in 2 of the included studies, the study population consisted of both heart failure patients and patients with chronic heart disease. Although it is known that a large part of heart failure diagnosis is secondary to chronic heart disease like hypertension and coronary heart disease [42], it would be ideal to compare the effect of influenza vaccination exclusively in a heart failure population and have undiluted results.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure (HF), affecting more than 2% individuals around the world, is a grave outcome in CHD patients ( 3 ). Moreover, high prevalence of HF as well as high hospital admission and mortality rates associated with HF has made it a compelling problem in the management of CHD patients ( 4 ). CHD patients with HF can exhibit several typical symptoms such as breathlessness, orthopnea, paroxysmal nocturnal dyspnea, and fatigue, whereas a considerable proportion of HF patients are misdiagnosed as having exacerbation of chronic obstructive pulmonary disease, atypical pneumonia, or other diseases with alike symptoms, which has led to diagnosis-related problems in clinical practice ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kondisi kronik yang ditemukan pada pasien PJK, seperti gagal jantung, juga meningkatkan risiko terjadinya depresi (Konrad et al, 2016). Sebanyak 44.2% pasien PJK mengalami gagal jantung (Morbach et al, 2017). Satu dari dua pasien gagal jantung dilaporkan mengalami depresi (Mbakwen, Aina, & Amadi, 2016).…”
Section: Penyakitunclassified